Management of Congenital Clinical Anophthalmos with Orbital Cyst: A Kinshasa Case Report - Thomas Stahnke; Andreas Erbersdobler; Steffi Knappe; Rudolf F. Guthoff; Ngoy J. Kilangalanga (Case Reports in Ophthalmological Medicine)
An early developmental lack of the optic vesicle can result in congenital anophthalmia, defined as a complete absence of the eye, which can be distinguished from congenital microphthalmos, where ocular rudiments are present. Here, a rare pediatric case of congenital clinical anophthalmos with orbital cyst in the left orbit is reported. The patient was a 14-month-old girl with no other congenital defects who underwent surgical and prothetic management in St. Joseph’s Hospital Kinshasa, Democratic Republic of the Congo (DRC). Surgery was carried out under general anesthesia. The cyst was punctured and its wall fully excised. Near the orbital apex pigmented elements representing iris, ciliary body, and choroidal or retinal remnants were found. The specimens were fixed in formalin for histological examination. Surgical cyst removal including socket deepening for an artificial eye was performed. Postoperative wound healing was uneventful and a satisfactory cosmetic outcome was achieved in all follow-up examinations. Histological examination revealed rudimentary ocular structures similar to degenerated lens tissue with a typical, PAS-positive capsule. Additionally, pigmented epithelial structures, which seem to be of ciliary body, iris, and choroidal or retinal-type epithelium origin, could be detected, prompting the final diagnosis, microphthalmia with dominant cyst formation.